(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Tonsillitis is one of the most common infectious and inflammatory diseases of the upper respiratory tract, characterized by involvement of the palatine tonsils and a tendency toward a recurrent course. The disease is widely observed in both children and adults and may lead to the development of local as well as systemic complications. Due to clinical polymorphism and the similarity of its symptoms to other oropharyngeal disorders, timely and accurate diagnosis of tonsillitis is of particular importance. This paper reviews the main laboratory diagnostic methods, including complete blood count, biochemical markers of inflammation, as well as microbiological, immunological, and molecular genetic techniques.